2016
DOI: 10.3892/br.2016.646
|View full text |Cite
|
Sign up to set email alerts
|

Impact of genotype on endocrinal complications in β-thalassemia patients

Abstract: In β-thalassemia, certain mutations cause a complete absence of β-globin chain synthesis, termed β-thalassemia, while others may allow certain β-globin production and are termed β- or β-thalassemia. The homozygous state results in severe anemia, which requires regular blood transfusion. By contrast, frequent blood transfusion can in turn lead to iron overload, which may result in several endocrinal complications. The present study aimed to investigate the impact of genotype on the development of endocrine comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 32 publications
4
24
1
Order By: Relevance
“…Two studies [6, 7] were excluded due to the duplicated publication. Finally, of 51 full-text articles, only 42 studies were included in this meta-analysis [25, 845]. In addition, two studies were identified from reference lists [46, 47].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Two studies [6, 7] were excluded due to the duplicated publication. Finally, of 51 full-text articles, only 42 studies were included in this meta-analysis [25, 845]. In addition, two studies were identified from reference lists [46, 47].…”
Section: Resultsmentioning
confidence: 99%
“…The selection flow chart is shown in Figure 1. Of the included studies, seven studies [30, 33, 34, 36, 39, 40, 43] were from Italy; seven studies [14, 16, 18, 20, 21, 31, 42] were from Iran; five studies [17, 19, 27, 44, 45] were from Egypt; five studies [4, 8, 22, 23, 35] were from the China region, including the mainland [22], Hong Kong [23], and Taiwan [4, 8, 35]; three studies [11, 12, 32] were from India; two studies [41, 47] were from Arabia; one study [37] was from Germany. The other studies were from Australia [26], Brazil [3], France [9], Lebanon [41], Oman [15], Turkey [25, 38], the United Kingdom [46], and the United States of America [2].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, due to the multifactorial causes of endocrine disorders in BTM patients, other factors such as: duration and adherence to prescribed chelation regimens, transfusional iron burden and biological responsiveness to a given chelation regimen could play an additional role in determining the degree of iron overload and development of organs damage. 13 16 …”
Section: Discussionmentioning
confidence: 99%